Coordinated inflammation and immune response transcriptional regulation in breast cancer molecular subtypes - Velazquez-Caldelas, Tadeo Enrique; Zamora-Fuentes, Jose Maria; Hernandez-Lemus, Enrique (Frontiers in Immunology, 2024)
Breast cancer is a complex and diverse disease, presenting challenges in understanding its underlying biology. In this study, we conducted a thorough analysis of gene composition and functional patterns in breast cancer subtypes and normal breast tissue using gene co-expression network analysis. Our aim was to uncover detailed immunological features distinguishing these tumors at the transcriptional level and their implications for diagnosis and treatment.Our analysis identified nine distinct gene module clusters, each representing a unique transcriptional signature within breast cancer subtypes and normal tissue. Notably, some clusters showed a high similarity in gene composition between normal tissue and its subtypes, whereas other exhibited lower similarity and shared traits. Each cluster provided insight into immune responses within breast cancer subtypes, indicating the presence of diverse immunological functions, including innate and adaptive immune responses. These findings enhance our understanding of the molecular mechanisms underlying breast cancer subtypes and offer insights into their unique characteristics. The identified immunological signatures have potential implications for diagnostic and therapeutic approaches. Moreover, the network-based approach introduced in this study offers a valuable framework for understanding the complexities of other complex diseases and elucidating their underlying biology.